Analisis Kontribusi Pendapatan Obyek Wisata Kawasan Luar Pura Uluwatu Terhadap Kemandirian Fiskal Pemerintahan Desa Adat Pecatu - Suwindu, I Wayan; Sibarani, Mentiana (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the contribution of four main sources of revenue, namely ticket fees, parking, pre-wedding permits, and profit sharing from the Kecak Dance performance managed through the Uluwatu Temple Tourism Area, to the fiscal independence of Pecatu Traditional Village. The research approach uses quantitative methods with descriptive and associative designs, based on secondary data from financial reports over ten years (2015–2024). The results indicate that revenue from the Uluwatu Temple Tourism Area significantly contributes to the Original Income of Pecatu Traditional Village (PAD), with an average contribution of 67.39% of the village's total revenue each year. Retribution tickets have become the dominant contributor, followed by parking revenue, pre-wedding permits, and Kecak Dance, which show a stable growth trend and support the diversification of village income. Fiscal independence indicators, such as the ratio of Local Own Revenue (PAD) to total village income, the effectiveness of village spending, and the ability to finance programs without external funds, consistently remain in the high category. These findings support the theories of Local Revenue Generation, Revenue Diversification, and Community-Based Tourism (CBT), which emphasize the importance of empowering local communities, strengthening village institutions, and managing tourism assets based on local wisdom. Strategies to strengthen the institution of the Management Agency, the implementation of ticket and parking digitalization, and integrated promotion of pre-wedding tourism potential are key supporting factors for the sustainability of village income.